2015
DOI: 10.1002/jbm.a.35625
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Mg particles into PDLLA regulates mesenchymal stem cell and macrophage responses

Abstract: In this work, we investigated a new approach to incorporate Mg particles within a PDLLA matrix using a solvent‐free commercially available process. PDLLA/Mg composites were manufactured by injection moulding and the effects of Mg incorporated into PDLLA on MSC and macrophage responses were evaluated. Small amounts of Mg particles (≤1 wt %) do not cause thermal degradation of PDLLA, which retains its mechanical properties. PDLLA/Mg composites release hydrogen, alkaline products and Mg2+ ions without changing pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 37 publications
4
31
0
Order By: Relevance
“…In another study, Mg particles were mixed in a PDLLA matrix to enhance MSC viability and osteogenic differentiation. The dissolution of Mg ions from composites was proven to be able to regulate the macrophage-induced inflammatory response evoked by PDLLA degradation components [ 145 , 146 ]. However, micron-size magnesium particles could be engulfed by macrophages, resulting in the necrosis of macrophages and the release of inflammatory cytokines [ 147 ].…”
Section: Harnessing the Power Of Macrophages For Enhanced Osteogenesimentioning
confidence: 99%
“…In another study, Mg particles were mixed in a PDLLA matrix to enhance MSC viability and osteogenic differentiation. The dissolution of Mg ions from composites was proven to be able to regulate the macrophage-induced inflammatory response evoked by PDLLA degradation components [ 145 , 146 ]. However, micron-size magnesium particles could be engulfed by macrophages, resulting in the necrosis of macrophages and the release of inflammatory cytokines [ 147 ].…”
Section: Harnessing the Power Of Macrophages For Enhanced Osteogenesimentioning
confidence: 99%
“…Contrary to 45S5 BAG, 1393 BAG is composed of additional K + and Mg 2+ ions. Previous studies have already reported on the positive effects of magnesium ions on cell viability, proliferation, and spreading . Furthermore, it is well documented that hMSCs express cationic channels on their cell membrane and that K + , Na + , and Ca 2+ channels are involved in cell proliferation, migration and differentiation .…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have already reported on the positive effects of magnesium ions on cell viability, proliferation, and spreading. 41 Furthermore, it is well documented that hMSCs express cationic channels on their cell membrane and that K 1 , Na 1 , and Ca 21 channels are involved in cell proliferation, migration and differentiation. 42,43 The blocking of Na 1 channels, for instance, increases hMSC proliferation, while blocking calciumactivated K 1 channels results in diminished hMSC proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies suggest that Mg ions have the potential to enhance the cell response in the initial phase of the osseointegration process [ 46 , 47 ]. Moreover, Cifuentes et al [ 48 ] have shown that by including small amounts of Mg particles into a poly-D-L-lactic acid (PDLLA) matrix, stimulation of fibronectin production, ALP activity and vascular endothelial growth factor secretion was induced in human bone marrow-derived mesenchymal stem cells as well as a reduction of the inflammatory response exhibited by human THP-1 macrophages.…”
Section: Discussionmentioning
confidence: 99%